Persepsi terhadap Kualitas Layanan, Kepuasan dan Loyalitas Konsumen - Zahra, Syarifa (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2012)
Abstract. The present study attempted to find out the relationship between customers’ perception towards quality of services and customer satisfaction with their loyalty. To collect the data, researcher assigned about 100 customers of Prodia as the subjects of the research who undertook their laboratory check up at the Clinic of Prodia Malang. All data were analyzed by using regression technique and then partial correlation analysis. The results of regression analysis showed that there was a significant relationship between customers’ perception towards quality of services and customers’ satisfaction towards customers’ loyalty). Meanwhile, the result of partial correlation analysis indicated that there was a positive correlation between qualities of services and customers’ loyalty. However, there was no correlation between customers’ satisfaction and loyalty of customers. The contribution given by customers’ perception towards quality of services and customer satisfaction with costumers’ loyalty is 59,8%.Keywords: Perception on quality of services, Customers, Satisfaction, Loyalty.